A Pongamia pinnata pods based activated carbon as an efficient scavenger for adsorption of toxic Co(II): kinetic and thermodynamic study. Issue 16 (1st November 2020) - Patil, Suryakant A.; Patil, Sandip K.; Sartape, Ashish S.; Bhise, Sagar C.; Vadiyar, Madagonda M.; Anuse, Mansing A.; Kolekar, Sanjay S.
ABSTRACT: A porous and high surface area-activated carbon based on Pongamia pinnata pods (PPP) was synthesized using a chemical method. The synthesized material was characterized using FTIR, XRD, BET, SEM, EDX, XPS and TGA. Plausible adsorption mechanism of Co(II) on PPPAC was evaluated systematically. The effect of various contributing parameters were investigated through batch adsorption experiments. Results reveal that the equilibrium was attained within 360 min having 0.35 g PPPAC amount at pH 6 and the maximum equilibrium capacity was observed 190.30 mg/g. Kinetically adsorption of Co(II) was best described by pseudo-second-order-model. The equilibrium data well suited with the Langmuir isotherm model and thermodynamic parameters indicate that the process was spontaneous and endothermic in nature. Graphical Abstract: An inexpensive strategy for waste-to-useful for preparation of porous high surface area-activated carbon using concentrated H2 SO4 as an impregnated reagent.